Multi-attribute Decision Analysis in GIS: Weighted Linear Combination and Ordered Weighted Averaging - Drobne, S.; Lisec, A. (Informatica)
Multi-attribute Decision Analysis in GIS: Weighted Linear Combination and Ordered Weighted Averaging